(untitled) (London Journal of Research In Science: Natural and Formal, 2024)
Humans are an amalgamation of matter and spirit (Liu, 2024.8a). They are a combination of the three- dimensional universe and the zero-dimensional universe (Liu, 2024.5). Humans have two origins: the origin of the spirit and the origin of the body (Liu, "?????"). The return to the origin of the spirit is called the death of the human body; the return to the origin of the body is called the death of the flesh. Humans are computer-like materials created by the universe, and the human spirit is software installed by the universe. The existence and survival of humans are determined by the universe and by themselves.